Comments on the EU Commission's capital markets union project - Volker Brühl; Helmut Gründl; Andreas Hackethal; Hans-Helmut Kotz; Jan Pieter Krahnen; Tobias Tröger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The European Commission has published a Green Paper outlining possible measures to create a single market for capital in Europe. Our comments on the Commission's capital markets union project use the functional finance approach as a starting point. Policy decisions, according to the functional finance perspective, should be essentially neutral (agnostic) in terms of institutions (level playing field). Our main angle, from which we assess proposals for the capital markets union agenda, are information asymmetries and the agency problems (screening, monitoring) which arise as a result. Within this perspective, we make a number of more specific proposals.
urn:nbn:de:hebis:30:3-372677
Keywords: 330; Capital Markets Union; functional finance approach; level playing field; financial services